APPLICATIONS OF MOLECULAR BIOLOGY IN THE DIAGNOSIS OF GENETIC DISEASES (CIPEEX, 2025)
Molecular biology has established itself as an essential tool for advancing research on the human genome, contributing to our understanding of how genes function under normal and pathological conditions. In the clinical field, molecular diagnosis has made it possible to identify genetic mutations associated with various diseases, promoting a more accurate and less invasive approach. The objective of this study was to describe the use of molecular biology in the diagnosis of genetic diseases, highlighting factors related to its laboratory application and its relevance for obtaining faster and more reliable diagnoses. This is an integrative review of the literature, conducted through searches in the PubMed and SciELO databases. Articles published in the last five years, in Portuguese and English, that addressed the proposed theme were included, excluding those that did not meet the established criteria. Genetic and molecular diagnosis allows changes in DNA to be identified even before symptoms appear, facilitating early detection of diseases and the development of targeted therapies. Among the main methods used are: karyotyping, indicated for the identification of large chromosomal alterations; PCR (Polymerase Chain Reaction), which enables the selective amplification of DNA segments and is widely used for its speed and sensitivity; sequencing, capable of detecting specific mutations with high precision, which is essential in the analysis of specific genes and in the diagnosis of hereditary syndromes; and array technologies, aimed at the simultaneous screening of multiple genomic regions with high sensitivity, especially in cases that require large-scale comparative analyses. Each technique has advantages and limitations that determine its clinical applicability. Karyotyping, although useful in the overall analysis of the genome, has low resolution for minor changes. PCR, in turn, depends on the choice of target sequences, limiting its exploratory nature. Sequencing, despite its accuracy, can still be costly in some contexts. Arrays do not identify specific mutations, but are effective in detecting variations in gene copy numbers. Thus, the methods are often applied in a complementary manner, increasing diagnostic coverage. The integration of these approaches strengthens clinical practice, enabling everything from early diagnosis to the monitoring of asymptomatic carriers. In addition, it provides support for genetic counseling, which is essential for couples at risk of transmitting hereditary mutations. This perspective reinforces the role of personalized medicine, which combines genomic information with therapeutic and preventive planning, enabling more effective strategies for tackling genetic diseases. It can be concluded that molecular biology applied to clinical diagnosis represents a significant advance in the detection and prevention of hereditary diseases. By enabling rapid, accurate, and targeted analyses, it contributes to reducing morbidity and mortality, guiding therapeutic decisions, and expanding the scope of genetic counseling. Its consolidation as a routine laboratory practice reinforces the relevance of preventive medicine and personalized healthcare.
Keywords: Human Genetics; Molecular Biology; Genome; Molecular Pathology